Design of urban and rural elderly care public areas integrating person-environment fit theory - Han Shuai (Nonlinear Engineering)
With the aggravation of the global aging process, providing a suitable living environment for the elderly has become an urgent issue. Based on the theory of human-environment adaptation, this study proposes a multilevel aging-friendly design scheme, aiming to improve the adaptability of urban and rural retirement public areas and the quality of life of the elderly. Through field research and questionnaire surveys, the impact of key design elements such as spatial layout, road design, lighting configuration, and resting area setup is investigated, taking into account the needs of the elderly in urban and rural areas of Chengdu. The results of the study reveal that spatial design has the most significant impact on the adaptability of the elderly, boasting a regression coefficient of 0.34. Road design, lighting design, and seating design also contribute, with regression coefficients of 0.27, 0.22, and 0.19, respectively. These findings indicate that various design elements play a crucial role in improving the convenience of activities, safety, and social interaction for the elderly. The adjusted R 2 of the overall model is 0.72, indicating that the explanatory power of the design elements on the adaptability of the elderly is strong. The study provides a theoretical basis and practical guidance for the design of aging-friendly public areas for the elderly, which has high social value and application prospects.